Romance Formula Potrayed in The Gift of The Magi Short Story by O. Henry - Firsta, Fanisa Zahrani; Salsabila, Nadira; Rohmana, Wahyu Indah Mala (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This research aims to find out how romance formulation is applied in shaping the storyline of